Sarcosine oxidase composite screen-printed electrode for sarcosine determination in biological samples - Rebelo, Tânia S. C. R. (2014)
As the prostate cancer (PCa) progresses, sarcosine levels increase both in tumor cells and urine samples, suggesting that this metabolite measurements can help in the creation of non-invasive diagnostic methods for this disease. In this work, a biosensor device was developed for the quantification of sarcosine via electrochemical detection of H2O2 (at 0.6 V) generated from the catalyzed oxidation of sarcosine. The detection was carried out after the modification of carbon screen printed electrodes (SPEs) by immobilization of sarcosine oxidase (SOX) on the electrode surface. The strategies used herein included the activation of the carbon films by an electrochemical step and the formation of an NHS/EDAC layer to bond the enzyme to the electrode, the use of metallic or semiconductor nanoparticles layer previously or during the enzyme immobilization. In order to improve the sensor stability and selectivity a polymeric layer with extra enzyme content was further added. The proposed methodology for the detection of sarcosine allowed obtaining a limit of detection (LOD) of 16 nM, using a linear concentration range between 10 and 100 nM. The biosensor was successfully applied to the analysis of sarcosine in urine samples.